Frequency Distribution of Natural Radionuclides in Talok Samilae Beach Sand at Pattani Province - สุขแก้ว, อดุลย์สมาน; อินตัน, ไมมูน; ดอเลาะ, ไซนับ (YRU Journal of Science and Technology, 2018)
The frequency distribution of specific activities of natural radionuclide (40K,226Ra และ232Th) beach samples sand Talok Samilae area in 24 samples have been studied, measured and analyzed. It was found that the frequency distribution of specific activities of natural radionuclides were asymmetrical distribution with the skewness of 0.86, 0.33 and 1.07 and the median values of 2,768.88, 161.75 and 94.46 Bq/kg, respectively Furthermore, four radiological hazard indices were evaluated for this area by using median values. Moreover, the results were also compared with the Office of Atoms for Peace (OAP) annual report data, global radioactivity measurement and evaluations by UNSCEAR.